PENINGKATAN HASIL BELAJAR MATERI CIRI-CIRI SEGITIGA MELALUI GAME BASED LEARNING BERBANTUAN UT-JI KELAS V SD - Indah Nur Arifah; Mohamad Aminudin; Mohamad Lukman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics instruction requires teaching models and media that can actively engage students so that the concepts being taught can be better understood. This study aims to improve student learning outcomes on the characteristics of triangles through the application of a Game-Based Learning (GBL) model supported by the “Snakes and Ladders: Exploring Science” (UT-JI) media. This study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles, preceded by a pre-cycle phase. The research subjects were 24 fifth-grade students in Class V B at Al Azhar 25 Islamic Elementary School in Semarang. Data were collected through tests, observations, and documentation, and then analyzed using quantitative and qualitative descriptive analysis. The results of the study show that the percentage of students achieving mastery increased from 33.33% in the pre-cycle—with an average score of 61.45—to 66.67% in Cycle I—with an average score of 73.75—and further increased to 91.67% in Cycle II—with an average score of 89.58. The results indicate that the implementation of a Game-Based Learning model using the “Snakes and Ladders: Exploring Science” (UT-JI) media is effective in improving student learning outcomes on the characteristics of triangles in Grade 5B at Al Azhar 25 Islamic Elementary School in Semarang.